Sustainable biopolymer-based spheres for controlled release of nematodes: from development to their effects under seasonal climate variations - Caballero, Javier Pitti; Collantes, Rubén; Antunes, Débora R. [UNESP]; Samaniego, Jahzeel; Santamaría, Yabelys; Muñoz, Jorge; Grillo, Renato [UNESP] (Elsevier, 2025)
The growing challenges of global food security, intensified by climate change and unsustainable agricultural practices, necessitate the development of innovative, environmentally sustainable pest management strategies. This study evaluates the efficacy of alginate- and chitosan-based biopolymer encapsulation systems, augmented with cellulose and encapsulated nematodes (oscheius carolinensis), as viable solutions for sustainable pest control in vegetable cultivation. The formulations were engineered to enable the controlled release of biocontrol agents, optimizing plant growth under varying seasonal climatic conditions (rainy, dry, and transitional seasons). Alginate matrices crosslinked with calcium chloride exhibited significant stability and controlled-release capabilities in the dry season. In contrast, chitosan matrices crosslinked with sodium tripolyphosphate exhibited rapid degradation in the same season. The encapsulation of nematodes favored the degradation of some spheres, while the presence of cellulose reduced their disintegration, prolonging the release of the organisms and reducing their viability in the soil. Tests with lettuce plants showed better development in the rainy season with little variation between treatments. Therefore, this study showed that the influence of environmental factors and the materials used to prepare polymeric spheres interfere with their effect on the soil. These results offer a promising strategy for reducing chemical pesticide reliance, increasing crop yields, and advancing sustainable agricultural practices.
Keywords: Alginate; Biopolymer encapsulation; Chitosan; Controlled release; Nematodes; Pest management; Seasonal variability; Sustainable agriculture